Trauma Exposure and Posttraumatic Stress Disorder in Adults with Severe Mental Illness: A Critical Review - Grubaugh, Anouk L. (2011)
There is a great deal of research on the prevalence, correlates, and treatment of PTSD in the general population. However, we know very little about the manifestation and consequences of PTSD in more complicated patient populations. The purpose of the current paper is to provide a comprehensive review of PTSD within the context of severe mental illness (SMI; i.e., schizophrenia spectrum disorders, mood disorders). Extant data suggest that trauma and PTSD are highly prevalent among individuals with SMI relative to the general population, and both are associated with adverse clinical functioning and increased healthcare burden. However, trauma and PTSD remain overlooked in this population, with low recognition rates in public-sector settings. Additionally, there are few data on the clinical course and treatment of PTSD among individuals with SMI. Particularly lacking are longitudinal studies, randomized controlled treatment trials, and studies using ethno-racially diverse samples. Furthermore, there is a need to better understand the interplay between trauma, PTSD, and severe forms of mental illness and to further develop and disseminate evidence-based PTSD treatments in this population. The current state of the literature and future directions for practice are discussed.